A Frustrated Lewis Pair Solution to a Frustrating Problem: Mono-Selective Functionalization of C–F Bonds in Di- and Trifluoromethyl Groups - Gupta, Richa; Jaiswal, Amit K.; Mandal, Dipendu; Young, Rowan D. (Synlett, 2020)
Polyfluoromethyl groups generally suffer from over-reaction, where multiple C–F bonds are uncontrollably functionalized. The use of a frustrated Lewis pair (FLP)-mediated C–F bond activation permits selective monodefluorination through base capture of intermediate fluorocarbocations. FLP-mediated C–F bond activation can be applied to aromatic, heteroaromatic, or nonaromatic difluoro and trifluoromethyl groups to generate selectively fluoride-substituted phosphonium and pyridinium salts. These salts can be further functionalized by Wittig coupling, nucleophilic substitution, photoredox alkylation, nucleophilic transfer, or hydrogenation reactions to install a range of functional groups into the activated C–F position.1 Introduction2 Frustrated Lewis Pair C–F Activation3 Conclusion
Keywords: frustrated Lewis pair; C–F bond activation; trifluoromethyl compounds; difluoromethyl compounds; selective activation